New Stabilization for Dynamical System with Two Additive Time-Varying Delays - Lianglin Xiong; Fan Yang; Xiaozhou Chen (The Scientific World Journal)
This paper provides a new delay-dependent stabilization criterion for systems with two additive time-varying delays. The novel functional is constructed, a tighter upper bound of the derivative of the Lyapunov functional is obtained. These results have advantages over some existing ones because the combination of the delay decomposition technique and the reciprocally convex approach. Two examples are provided to demonstrate the less conservatism and effectiveness of the results in this paper.